Investigation of the in vitro performance difference of drug-Soluplus® and drug-PEG 6000 dispersions when prepared using spray drying or lyophilization - Mohammad A. Altamimi; Steven H. Neau (Elsevier, 2017)
Purpose: To evaluate the physicochemical and in vitro characteristics of solid dispersions using BCS II model drugs with Soluplus® and one of its component homopolymers, PEG 6000. Methods: Nifedipine (NIF) and sulfamethoxazole (SMX) of 99.3% and 99.5% purity, respectively, were selected as BCS II model drugs, such that an improved dissolution rate and concentration in the gastrointestinal tract should increase oral bioavailability. Soluplus® is an amorphous, tri-block, graft co-polymer with polyvinyl caprolactam, polyvinyl acetate, and polyethylene glycol (PCL:PVAc:PEG6000) in the ratio 57:30:13. PEG 6000 (BASF) is a waxy material with melting point of about 60 °C. Solid dispersions were prepared using lyophilization or spray drying techniques. Dissolution study, crystallinity content, and analysis for new chemical bond formation have been used to evaluate the dispersed materials. Results: Although each polymer improved the drug dissolution rate, dissolution from Soluplus® was slower. Enhanced dissolution rates were observed with NIF solid dispersions, but the dissolution profiles were quite different due to the selected technique, polymer, and dissolution medium. For SMX, there was similarity across the dissolution profiles despite the medium, polymer, or applied technique. Each polymer was able to maintain an elevated drug concentration over the three hour duration of the dissolution profile, i.e., supersaturation was supported by the polymer. DSC thermograms revealed no melting endotherm, suggesting that the drug is amorphous or molecularly dispersed. Conclusion: NIF and SMX solid dispersions were successfully prepared by spray drying and lyophilization using Soluplus® or PEG 6000. Each polymer enhanced the drug dissolution rate; NIF dissolution rate was improved to a greater extent. Dispersions with PEG 6000 had a faster dissolution rate due to its hydrophilic nature. DSC analysis showed that no crystalline material exists in the dispersions.